Modos de presença do novo na comunicação automobilística: regimes de interação, regimes de sentido - Ciaco, João Batista Simon (2010)
The central subject of this assignment consists in the study of the presence of the new in the contemporary communication and its consequent regimes of interaction and sense in the continuity and discontinuity movements of the advertising discourses, as well as its impacts in the construction, permanence and reelaboration of brand identities managed by companies. The study aims to comprehend how these regimes of interaction and sense are organized in the automotive advertising through the practices that reveal and explicit, on one hand, the own statute of the new within the discourse and, on the other, the strategic communication choices of the enterprises. The object of the study is the advertising communication, being ads from the automotive industry in the last years propagated in several kinds of media our corpus of analysis. The theoretic referential is the discursive semiotics, developed from the postulations of A.J.Greimas and his collaborators, in special the sociosemiotics, that takes care of the social dimension of discourse, being considered on its recent developments disseminated in Brazil mainly through the Centro de Pesquisas Sociossemióticas (CPS). A major emphasis is put on semioticians that work with advertising and marketing, as Jean-Marie Floch, Andrea Semprini, Gianfranco Marrone and Ana Claudia de Oliveira, being the late works of Eric Landowski the basilar and essential references for approaching the regimes of interaction and sense. In spite of being an inflection of discontinuity in the communication, turning the before disforic and making the after positive, the excessive and recurrent presence of the new seems to tend it towards desemantization, being our hypothesis that the new operates, in its iteracy, much more such as a qualificator of permanence than of rupture. Even being pertinent and relevant for cross media and multimedia advertising, the manners of presence of the new analysis in the enunciator and in the enunciation clarifies that the regimes of interaction organized by the new structure paths of sense that always turn into the accident regime (interactions governed by the logic of randomness) and into the programming regime (interactions governed by the logic of regularity), both regimes where the sense of the new gradually disappears. In conclusion, it is possible to affirm that this permanence of the new, reinvigorated through the renewed figurative covering produced by the advertising discourse, has legitimated the interconnections through the whole (the brand) and the parties (the products) in the edification of identity simulacrum of the brand in the auto communication. We expect this work supports progressing the study of syncretism and interaction in the semiotics area and the cross media and multimedia in communication one, besides bringing together the semiotics and the marketing in order to build a more consistent and further vision in producing business communication strategies